MAP symbol estimation on frequency-flat Rayleigh fading channels via a Bayesian EM algorithm. - Chiavaccini, E. (IEEE Transactions on communications)
In this paper, an expectation-maximization (EM) technique for maximum a posteriori estimation is employed to devise novel soft-in soft-out algorithms for symbol detection over frequency-flat Rayleigh fading channels. An application of these algorithms to iterative decoding of coded PSK signals is proposed and some performance results are illustrated